Pengaruh Penggunaan Beton Ramah Lingkungan Terhadap Kekuatan Dan Ketahanan Struktur Bangunan - Harashta (Jurnal Ilmu Teknik Sipil Indonesia, 2025)
This study analyzes the effect of using green concrete on the strength and durability of building structures through a comprehensive literature review. Green concrete, which utilizes waste materials such as fly ash, slag, and silica fume as cement substitutes, and recycled concrete aggregate (RCA), offers a solution to reduce the ecological impact of the construction industry. The analysis shows that while cement substitution can decrease the early strength of concrete, its long-term strength tends to be equivalent to or even exceed that of conventional concrete. Specifically, the use of silica fume is proven to significantly increase compressive strength. Furthermore, green concrete demonstrates enhanced durability against chemical attacks such as chloride and sulfate, which effectively extends the service life of structures. Although challenges exist in material standardization and property variability, these findings confirm that green concrete is a reliable and sustainable alternative. This research concludes that the adoption of this material not only supports sustainable development but also provides significant technical benefits in terms of long-term structural strength and durability.